Conceptualizing the dialogical structure of mass communication: A comparison of the dialogical networks and mediated social communication approaches. (December 2021) - Baumgartner, Antonia; Fürst, Silke; Schönhagen, Philomen
Highlights: Linking media studies and ethnomethodology enriches research on mediated dialogues. Journalistic mediation enables a discourse between dispersed members of society. The roles of speaker and addressee in discourse are interchangeable. Actors usually do not speak only for themselves but represent a social group. Future studies should examine media coverage via relational content analysis. Abstract: Theoretical contributions conceptualizing dialogical processes and structures of mass communication are scattered, hence different disciplines work on the same issues without uniting their potentials. The mediated social communication (MSC) approach developed by German communication scholars and the dialogical network (DN) approach informed by ethnomethodology and conversation analysis share important characteristics. This paper contributes to interdisciplinary research by comparing the approaches, analyzing their similarities and differences, and discussing their integration. The MSC approach offers additional theoretical considerations; the DN approach provides pointers to the empirical analysis of dialogical structures in mass communication. Essentially, both approaches conceptualize journalists as mediators of the exchange between diverse (individual or collective) actors speaking for social groups. This journalistic mediation of various statements enables a shared society-wide discourse essential for the existence of any society. However, the actual performance of this mediation varies between countries and depends on editorial practices, norms, and resources, which differ across media types and outlets. Future research could use the theoretical conceptualizations of these approaches to investigate communicative actor relations more thoroughly and focus on how they develop in the context of journalistic mediation.